Traffic-based floor preference for the scheduling of elevators in elevator group control system - Malan Dipak Sale; V. Chandra Prakash (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Modern high-rise buildings require complex yet efficient Elevator Group Control Systems (EGCSs). In vertical transportation through an elevator, a passenger must make a hall call by pressing a landing call button installed at each floor and located near the cars of the elevator group. Conventionally, the EGCS allocates one of the cars for each hall call. Waiting time for the arrival of car and journey time inside a car are two parameters, which provide a suitable measure for quality and efficiency of EGCSs. The proposed system deals with this car-call allocation problem. The proposed work analyzes the generated traffic patterns to dispatch a certain number of cars to certain floors in order to reduce overall wait time of passengers. The proposed algorithm is simulated for high-rise building with 20 floors and provides a better result with the reduced wait time for more number of passengers.